2022
DOI: 10.1021/acsanm.1c03045
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Nanopillar-Based Mechanobactericidal Systems

Abstract: The rise of multidrug-resistant bacteria is the biggest threat to human health globally, as described by the World Health Organization. Mechanobactericidal surfaces provide a sustainable approach to addressing this concern by eradicating pathogens, especially bacteria, “right-at-the-point” of contacting the surface. However, the lack of a “design to manufacture” approach due to our limited understanding of the mechanobactericidal mechanism has impeded engineering optimization to develop scalable exploitation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 110 publications
1
27
0
Order By: Relevance
“…Among these designs, nanopillars received the most attention because their puncture-based biocidal actions are material composition and bacterial species independent. The bactericidal mechanisms of such structures were already highlighted in a very recent review [ 224 ]. Additionally, there are several studies that demonstrated that titanium nanopillars with proper diameter, spacing, and height yield cell-selective surfaces.…”
Section: Innovative Designs To Mitigate Device-associated Infectionsmentioning
confidence: 99%
“…Among these designs, nanopillars received the most attention because their puncture-based biocidal actions are material composition and bacterial species independent. The bactericidal mechanisms of such structures were already highlighted in a very recent review [ 224 ]. Additionally, there are several studies that demonstrated that titanium nanopillars with proper diameter, spacing, and height yield cell-selective surfaces.…”
Section: Innovative Designs To Mitigate Device-associated Infectionsmentioning
confidence: 99%
“…However, the over-reliance on antibiotics in some areas, such as medicine and agriculture, has led to the development of bacterial resistance, making antibiotics less effective. [9][10][11][12][13] In order to prevent bacteria from developing drug resistance, many new antimicrobial materials have been developed to replace traditional antibiotics, such as polypeptides [14][15][16] and positively-charged antimicrobial materials. 5,[17][18][19][20] Some of the peptide-based antimicrobial materials can cause bacterial membranes to be ruptured rather than interact with the substances inside the bacteria, thus largely reducing the probability for bacteria to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the over-reliance on antibiotics in some areas, such as medicine and agriculture, has led to the development of bacterial resistance, making antibiotics less effective. 9–13…”
Section: Introductionmentioning
confidence: 99%
“…Developments in this field have been focused on replicating artificially these surfaces by different means on different materials, as summarized in recent reviews. [ 21–24 ] More recent works aim at adding extra functions by functionalizing these mechano‐bactericidal patterns with surface stimuli‐responsive polymeric brushes for releasing dead bacteria debris. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%